2011
DOI: 10.1186/1471-2334-11-316
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus genotype distribution in Madrid and correlation with cytological data

Abstract: BackgroundCervical cancer is the second most common cancer in women worldwide. Infection with certain human papillomavirus (HPV) genotypes is the most important risk factor associated with cervical cancer. This study analysed the distribution of type-specific HPV infection among women with normal and abnormal cytology, to assess the potential benefit of prophylaxis with anti-HPV vaccines.MethodsCervical samples of 2,461 women (median age 34 years; range 15-75) from the centre of Spain were tested for HPV DNA. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
3
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 29 publications
4
21
3
2
Order By: Relevance
“…An HPV test is also accepted as an adjunct to cytology in primary screening for women aged 30 years or older on the basis of results from cohort studies (Naucler et al, 2009;Said et al, 2009;Selva et al, 2009;Filipi et al, 2010;Uusküla et al, 2010 ). In our study, the concordance level for cytological and molecular tests was very low compared with other studies that found up to 68% correlation (Selva et al, 2009;Martín et al, 2011). However, these differences could be related to the efficiency of the different methodologies used to identify HPV in different regions of the world.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…An HPV test is also accepted as an adjunct to cytology in primary screening for women aged 30 years or older on the basis of results from cohort studies (Naucler et al, 2009;Said et al, 2009;Selva et al, 2009;Filipi et al, 2010;Uusküla et al, 2010 ). In our study, the concordance level for cytological and molecular tests was very low compared with other studies that found up to 68% correlation (Selva et al, 2009;Martín et al, 2011). However, these differences could be related to the efficiency of the different methodologies used to identify HPV in different regions of the world.…”
Section: Discussioncontrasting
confidence: 47%
“…Our study revealed a similar percentage of HPV-DNA to studies performed in Slovenia and West Africa (Jenko et al, 2011;Piras et al, 2011). However, a higher percentage of HPV was observed in North Sardinia, Italy (35.9%); Madrid, Spain (43.2%); France (45.3%); Rio Grande do Norte, Brazil (48%); Kuwait (51%); and Texas, USA (63%) (Pannier-Stockman et al, 2008;Fernandes et al, 2009;Al-Awadhi et al, 2011;Martín et al, 2011;Piana et al, 2011;Shen-Gunther and Yu, 2011). In contrast, a lower percentage of infection was found in studies in Sweden (7%) and Albania (15.1%) (Naucler et al, 2009;Filipi et al, 2010).…”
Section: Discussionmentioning
confidence: 58%
“…In Turkey, the HPV infection rate is 2%-6%. As in this study, global results demonstrated that HPV 16 was the most prevalent infection (28%), whereas HPV 18 was found more rarely (34). For example, in Venezuela HPV 16 was the most common type (60%), followed by HPV 18 (20%), HPV 6 (10%), and HPV 58 (10%) (36).…”
Section: Type Primersmentioning
confidence: 53%
“…For example, in Venezuela HPV 16 was the most common type (60%), followed by HPV 18 (20%), HPV 6 (10%), and HPV 58 (10%) (36). With the exception of East Africa, China, Japan, and Taiwan, HPV 16 is the most prevalent type in all parts of the world (34). Interestingly, HPV type 18 is detected at the same frequency all over the world.…”
Section: Type Primersmentioning
confidence: 98%
See 1 more Smart Citation